Combination Immune Therapies to Enhance Anti-Tumor Responses by NK Cells - James, Ashley M.; Cohen, Adam D.; Campbell, Kerry S. (Frontiers in Immunology, 2013)
Natural killer (NK) cells are critical innate immune lymphocytes capable of destroying virally infected or cancerous cells through targeted cytotoxicity and further assisting in the immune response by releasing inflammatory cytokines. NK cells are thought to contribute to the process of tumor killing by certain therapeutic monoclonal antibodies (mAb) by directing antibody-dependent cellular cytotoxicity (ADCC) through FcγRIIIA (CD16). Numerous therapeutic mAb have been developed that target distinct cancer-specific cell markers and may direct NK cell-mediated ADCC. Recent therapeutic approaches have combined some of these cancer-specific mAb with additional strategies to optimize NK cell cytotoxicity. These include agonistic mAb targeting NK cell activating receptors and mAbs blocking NK cell inhibitory receptors to enhance NK cell functions. Furthermore, several drugs that can potentiate NK cell cytotoxicity through other mechanisms are being used in combination with therapeutic mAb. In this review, we examine the mechanisms employed by several promising agents used in combination therapies that enhance natural or Ab-dependent cytotoxicity of cancer cells by NK cells, with a focus on treatments for leukemia and multiple myeloma.